2020
DOI: 10.1186/s13045-020-00882-6
|View full text |Cite
|
Sign up to set email alerts
|

Post-transplant cyclophosphamide after matched sibling, unrelated and haploidentical donor transplants in patients with acute myeloid leukemia: a comparative study of the ALWP EBMT

Abstract: Background: The use of post-transplant cyclophosphamide (PTCy) is highly effective in preventing graft-versus-host disease (GVHD) in the haploidentical (Haplo) transplant setting and is being increasingly used in matched sibling (MSD) and matched unrelated (MUD) transplants. There is no information on the impact of donor types using homogeneous prophylaxis with PTCy. Methods: We retrospectively compared outcomes of adult patients with acute myeloid leukemia (AML) in first complete remission (CR1) who received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 38 publications
6
61
1
Order By: Relevance
“…In patients with human leukocyte antigen identical sibling donors (ISDs), engraftment was faster ( 1 – 3 ), the relapse rate was lower ( 4 ), and the leukemia-free survival (LFS) rate was better in the PB group compared with the BM group, particularly for the patients with advanced stage disease ( 1 , 4 ). Similar results were also observed in patients with HLA-unrelated donors (URDs) ( 5 7 ). Considering the fact that PB stem cells (PBSCs) collection is a non-surgical procedure, PBSC transplantation (PBSCT) is more convenient and more acceptable for donors.…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…In patients with human leukocyte antigen identical sibling donors (ISDs), engraftment was faster ( 1 – 3 ), the relapse rate was lower ( 4 ), and the leukemia-free survival (LFS) rate was better in the PB group compared with the BM group, particularly for the patients with advanced stage disease ( 1 , 4 ). Similar results were also observed in patients with HLA-unrelated donors (URDs) ( 5 7 ). Considering the fact that PB stem cells (PBSCs) collection is a non-surgical procedure, PBSC transplantation (PBSCT) is more convenient and more acceptable for donors.…”
Section: Introductionsupporting
confidence: 76%
“…Bashey et al (31) analyzed outcomes from a multicenter study comparing HID HSCT with G-CSF-primed PB versus BM and showed the lower relapse risk after PBSCT was limited to patients with leukemia. Several studies also noted that PB grafts had protection against relapse in HID HSCT with PT-CY (7,11,31). However, in other studies, PB grafts were not associated with lower rates of relapse (8,9,12,32,37,38).…”
Section: A B D Cmentioning
confidence: 98%
“…This is especially challenging for minority patients [59][60][61]. As such, more and more institutions have begun implementing haploidentical (haplo) HCT [62][63][64][65][66][67][68][69][70]. This both increases donor availability and decreases delays involved in finding and collecting stem cells from an unrelated donor.…”
Section: Post-transplant Ben In Murine Modelsmentioning
confidence: 99%
“…This is in keeping with a previous study by the Blood and Marrow Transplant Clinical Trial Network, which compared triple PTCY-based prophylaxis to a control group of patients receiving a CNI and methotrexate regimen 10 : GVHD was reduced with the triple PTCY prophylaxis and relapse again was not affected. 10 A recent retrospective study by the EBMT has compared MUD and Haplo grafts in acute myeloid leukemia patients in first complete remission receiving PTCYbased prophylaxis 11 : again, GVHD and TRM were increased in Haplo grafts (hazard ratio [HR], 1.6 and 2.6, respectively), but relapse was reduced (HR, 0.7) as compared with MUD transplants, which translated into comparable leukemia-free survival.…”
mentioning
confidence: 99%